Irish Free State railway accounts - Mackie, John (Statistical and Social Inquiry Society of Ireland, 1936)
I propose in this short paper, which has been rather hurriedly prepared, to confine myself to the Financial Accounts of the Great Southern Railways and the Great Northern Railway for the years 1929, 1934 and 1935.
Read before Society on Thursday, the 30th April, 1936
Keywords: Railway infrastructure; Railway finance; 314.15